Primary Extragonadal Germ Cell Tumors in Klinefelter Syndrome: 10-Years of Experience from a Single Institute - Yura Kim; Won Kee Ahn; Jung Woo Han; Seung Min Hahn; Seung Yeon Kwon; Chuhl Joo Lyu (The Korean Society of Pediatric Hematology-Oncology, 2020)
Background : : Approximately 8% of male patients presenting with primary mediastinal germ cell tumors (GCTs) have Klinefelter syndrome (KS), while patients diagnosed with retroperitoneal GCTs also exhibit a range of chromosomal abnormalities. The exact mechanism underlying the development of GCTs in Klinefelter syndrome is unknown, but KS frequently goes underdiagnosed as a result of its varied symptoms and a low general awareness of this condition. Thus, the Children's Oncology Group recommends screening of Klinefelter syndrome in pediatric and adolescent male subjects who present with GCTs. Methods : : We retrospectively reviewed the medical records of extragonadal germ cell tumor patients treated at Severance hospital, department of pediatrics or division of pediatric hematology-oncology over the last ten years. Results : : A total of 95 patients with extragonadal germ cell tumors were included in this study. Karyotyping was done in eight patients out of 95 patients, three patients with KS and one patient with Down syndrome. Twelve of extragonadal GCT patients presented at mediastinum, with most common histology of mature teratoma, and three patients presented with chromosomal abnormalities, two with KS and one with Down syndrome. A total of nine patients were diagnosed with retroperitoneal GCTs and only one had KS. Conclusion : : We described the characteristics of 95 cases of extragonadal GCTs. Although the mechanism of extragonadal GCTs in KS is not clear, karyotyping in pediatric and adolescent extragonadal GCT patients could be helpful in figuring out chromosomal abnormalities including KS and their roles in GCT pathophysiology, which can contribute to improve one's health.